Conservation Challenges Imposed by Evolutionary History and Habitat Suitability Shifts of Endangered Freshwater Mussels under a Global Climate Change Scenario - Joaquim Reis; Silvia Perea; Mafalda Gama; Sofia L. Mendes; Vitor C. Sousa; Cristina Lima; Filipe Banha; Maria Gil; Maria Garcia Alvarez; Pedro Anastácio; Carla Sousa Santos; Rafael Araujo (Diversity, 2024)
Climate change and associated shifts in temperature and precipitation patterns have become an increasing concern as drivers of ongoing biodiversity loss. The Mediterranean region is particularly vulnerable, being both a biodiversity hotspot and a region very prone to desertification. Freshwater mussels are amongst the most threatened invertebrate taxa worldwide. Unio tumidiformis is an endemic and endangered species restricted to the southern Iberian Peninsula, living in temporary Mediterranean-type streams. Freshwater mussels need a fish host for successful larval transformation, meaning U. tumidiformis must belong to the genus Squalius. The main objective of this study was to evaluate the vulnerability of U. tumidiformis to climate change, by studying its population genetics and evolutionary history, its current and future habitat suitability, and that of its hosts. Genetic population structure and diversity were assessed using Single-Nucleotide Polymorphisms through Genotyping by Sequencing and used to infer species evolutionary history. The species potential distribution was modeled using an ensemble forecasting approach, and future shifts in habitat suitability were assessed with the projected climate data layers from Worldclim. Most populations showed extreme genetic differentiation (Fst up to 0.745), even from close neighboring ones. Upper Guadiana populations were more diverse and less differentiated. We hypothesize that U. tumidiformis originated in Upper Guadiana and followed the same colonization routes as their hosts with numerous founder effects and bottlenecks. Our results also predicted a reduction of 99% of climatically suitable areas for U. tumidiformis in the Iberian Peninsula until 2040. For the fish hosts, a maximum 42% reduction in suitable areas was estimated throughout the century, with remaining adequate habitats in the north. Our results suggest that difficult conservation options are necessary, prioritizing the preservation of populations, translocations to the northern area of its historical range and stream engineering to increase resilience to droughts.